Effect of a Brief CO₂ Exposure on Ethylene Production - Chaves, Alicia Raquel (1984)
Ethylene production and respiration by Granny Smith apples were inhibited by treatment with 20% CO₂ for 2 hours. A similar effect was observed in tissue slices when treated at either 0 or 25°C. The inhibition continued even after an extended aeration period. There is also an inhibition of ethylene emission in tissue slices incubated with exogenous 1-aminocyclopropane-1-carboxylic acid (ACC). In general, CO₂ treatment increased the ACC content of the tissue. These observations are consistent with the idea the action of CO₂ is directed toward the enzyme system responsible for the conversion of ACC into ethylene.